(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The purpose of the paper is to identify the main problems and barriers to the adoption of Industry 4.0 technologies that help to improve the OSH system in small business enterprises, and to develop scientifically based recommendations for their elimination. The current study employed a qualitative research approach using two methods. The first method was to identify the problem by conducting interviews with managers and labor protection specialists and employees of small businesses. The second method is to study various sources and research works related to the opportunities and challenges of using digital technologies to improve OSH. The results of the study provide a comprehensive overview of the range and list of barriers to small businesses’ willingness to use digital technologies and smart devices to ensure safe and decent working conditions. Also, this study substantiates that the use of Industry 4.0 technologies to improve working conditions in small business enterprises can bring high benefits for small business owners, employees and society.